Production process of super-strong freezing-resistant impervious artificial pavement brick
Through specific ratios and processes, expandable hydration products, hydrated calcium silicate gels and molecular network structures are generated, which solves the problems of poor frost resistance and easy damage in traditional pavement bricks, and achieves high-performance durability and permeability. It is suitable for infrastructure such as highways and airport runways.
Patent Information
- Application Number
- CN202510636170.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-08-22
AI Technical Summary
Traditional pavement tiles have poor frost resistance, are prone to cracking, have short life, low density, microporous water accumulation, easy to damage, and their performance declines rapidly in extreme climates.
The raw materials and processes with specific ratios are adopted, including cement, mineral blends, expansion agents, nanosilica and polymer emulsions, and the expansion hydration products, hydrated calcium silicate gels and molecular network structures are generated through reactions to improve the frost resistance, permeability and strength of the bricks.
The bricks have significantly improved the freezing resistance, permeability and durability. The bricks have no more than 15% compressive strength loss after freeze-thaw cycle, the water absorption rate is ≤3%, and the penetration depth is ≤5mm, adapting to extreme climate environments.
Smart Images

Figure CN120518355A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pavement brick manufacturing, in particular to a production process of super-freeze-resistant and anti-seepage artificial pavement bricks. Background Art
[0002] With the acceleration of urbanization and increasing traffic loads, the performance requirements for pavement materials are becoming increasingly demanding. Traditional pavement bricks, due to their insufficient durability, poor freeze-thaw resistance, and high water absorption, often break, deform, and leak under extreme weather conditions, impacting road life and driving safety. Therefore, developing high-performance artificial pavement bricks with superior freeze-thaw resistance, impermeability, and crack resistance has become a key research direction in materials science and engineering.
[0003] In the actual implementation process, there are still some problems:
[0004] 1. Traditional pavement bricks are generally not frost-resistant enough. In cold regions or areas with severe climate conditions, the bricks are prone to expansion and contraction during freeze-thaw cycles, leading to the formation and expansion of cracks. These cracks not only affect the appearance of the pavement bricks, but also reduce their mechanical strength and service life. Under prolonged freeze-thaw conditions, the pavement bricks may even completely crack or peel off.
[0005] 2. Because the cement matrix of traditional pavement bricks has a low density, they often contain numerous tiny pores within the bricks. These pores easily accumulate water and expand during freeze-thaw cycles, further increasing the risk of water penetration and structural damage. Once this water penetrates the bricks, the expansion of the water during freeze-thaw cycles can cause more severe cracks, making the bricks more susceptible to damage.
[0006] 3. Traditional pavement bricks have low strength, especially in extreme climates. They often deform and crack due to temperature fluctuations or long-term loads. Traditional cement has a high coefficient of thermal expansion, which can cause cracks in bricks in environments with large temperature fluctuations, affecting their stability and durability. Furthermore, over long-term use, bricks are susceptible to degradation due to external factors such as traffic loads and climate change, leading to a rapid decline in performance. Summary of the Invention
[0007] (1) Technical issues to be resolved
[0008] In order to solve the above problems of the prior art, the present invention provides a production process for super frost-resistant and anti-permeability artificial pavement bricks, which solves the problems of traditional pavement bricks such as poor frost resistance, easy cracking, short life, low density, water accumulation in micropores, and easy damage.
[0009] (2) Technical solution
[0010] In order to achieve the above object, the main technical solutions adopted by the present invention are:
[0011] A production process for super-strong frost-resistant and anti-permeability artificial paving bricks, comprising the following steps:
[0012] S1: Raw material preparation: Select the following raw materials and mix them according to mass percentage:
[0013] Cement: 25% to 35%, using P.O42.5 ordinary Portland cement;
[0014] Mineral admixture: 15% to 25%, either fly ash or slag;
[0015] High-strength aggregate: 30% to 45%, a mixture of quartz sand with a particle size of 1 to 3 mm and basalt crushed stone with a particle size of 5 to 10 mm;
[0016] Expansion agent: 2% to 4%, either bauxite or calcium bauxite;
[0017] Nano-silicon dioxide: 0.5% to 2%, with an average particle size of 15 to 30 nm;
[0018] Polymer emulsion: 1% to 3%, which is an acrylic polymer emulsion with a solid content of 45% to 50%;
[0019] Water: 12% to 16%;
[0020] S2: Mixing and stirring: pre-mix all the above raw materials according to the mass ratio, dry mix time is 90 seconds, stir in a forced concrete mixer to ensure uniform distribution of the ingredients, then add water and polymer emulsion, wet mix time is 120 seconds to form a uniform mixture;
[0021] S3: Molding: The mixture is molded by a hydraulic molding machine with a pressure of 25MPa to 30MPa and a pressing time of 8 seconds. The density of the brick after molding is 2.45g / cm 3 ~2.60g / cm 3 ;
[0022] S4: Curing: The formed pavement bricks are subjected to moist curing in an environment of 5℃~15℃, with the humidity maintained at 80%~90%. The curing time is 7 to 14 days;
[0023] S5: Performance test. After the curing period, the samples are subjected to compression test according to standard size. During the test, a compression testing machine is used to load the samples until they break. The qualified standard is that the compressive strength of the brick body should be ≥60MPa. The brick body is subjected to 50 freeze-thaw cycles in the freezing and heating cycle process. The freezing process is -18℃ and the melting process is +5℃. The cycle time is 1 hour freezing and 2 hours heating. The quality, compressive strength and appearance of the brick body are measured after each cycle.
[0024] The expansive agent reacts with water in the cement matrix to generate expansive hydration products, which fill the tiny pores in the cement matrix.
[0025] The nano-silicon dioxide reacts with calcium hydroxide in cement to generate calcium silicate hydrate, forming a dense gel network in the cement matrix.
[0026] The polymer emulsion forms a strong molecular network structure by undergoing a cross-linking reaction with cement hydration products.
[0027] The mineral admixture is either fly ash or slag, which is mixed with the Ca in cement. 2 +The reaction generates hydration products and reduces the thermal expansion coefficient of the brick by reducing the heat release of cement.
[0028] The mass ratio of the cement to the mineral admixture is:
[0029] The cement: mineral admixture ratio is 1:0.2 to 1:0.5, and the optimal mass ratio is 1:0.3.
[0030] After the mixture is formed under high pressure, the bending strength is ≥7MPa, and the compressive strength loss of the brick body does not exceed 15% after 50 freeze-thaw cycles.
[0031] The water absorption rate of the brick body within 24 hours is ≤3%, and the penetration depth does not exceed 5mm.
[0032] (3) Beneficial effects
[0033] The beneficial effects of the present invention are: through precise proportioning and the use of specific raw materials and their interaction, the frost resistance, impermeability, strength and durability of the brick body are significantly improved; by using specific expansion agents, nano-silica and polymer emulsion and other functional materials, the microstructure of the brick body can be effectively improved, so that the brick body maintains low mass loss and high compressive strength during the freeze-thaw cycle; in particular, after 50 freeze-thaw cycles, the brick body can ensure that its compressive strength loss does not exceed 15%, and no visible cracks appear, indicating that the pavement bricks manufactured by this process have excellent durability and adaptability to extreme climate environments. In addition, the mineral admixture used The material effectively reduces the thermal expansion coefficient of cement, thereby reducing the volume deformation caused by temperature changes, making the brick body more stable during long-term use. The water absorption rate of the brick body within 24 hours does not exceed 3%, and the penetration depth does not exceed 5mm, ensuring its excellent anti-seepage performance, thereby preventing freeze-thaw damage caused by water penetration. The pavement bricks manufactured by this production process not only have excellent mechanical properties, but can also effectively cope with complex conditions such as freeze-thaw cycles, water-rich environments and high-frequency traffic, ensuring its long-term and stable use in high-altitude cold areas and high-frequency traffic areas in cities, and are widely used in infrastructure construction such as highways, parking lots, and airport runways. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Schematic diagram of the process of the present invention;
[0035] Figure 2 This is a schematic diagram of the raw material ratio of the present invention;
[0036] Figure 3 A schematic diagram of the compressive strength of pavement bricks produced by the process of the present invention;
[0037] Figure 4 It is a schematic diagram of the ratio experiment of the present invention. DETAILED DESCRIPTION
[0038] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation methods in conjunction with the accompanying drawings.
[0039] Please refer to Figures 1 to 4 As shown, the production process of a super-strong frost-resistant and anti-permeability artificial pavement brick of the present invention comprises the following steps:
[0040] S1: Raw material preparation: Select the following raw materials and mix them according to mass percentage:
[0041] Cement: 25% to 35%, using P.O42.5 ordinary Portland cement;
[0042] Mineral admixture: 15% to 25%, either fly ash or slag;
[0043] High-strength aggregate: 30% to 45%, a mixture of quartz sand with a particle size of 1 to 3 mm and basalt crushed stone with a particle size of 5 to 10 mm;
[0044] Expansion agent: 2% to 4%, either bauxite or calcium bauxite;
[0045] Nano-silicon dioxide: 0.5% to 2%, with an average particle size of 15 to 30 nm;
[0046] Polymer emulsion: 1% to 3%, which is an acrylic polymer emulsion with a solid content of 45% to 50%;
[0047] Water: 12% to 16%;
[0048] S2: Mixing and stirring: pre-mix all the above raw materials according to the mass ratio, dry mix time is 90 seconds, stir in a forced concrete mixer to ensure uniform distribution of the ingredients, then add water and polymer emulsion, wet mix time is 120 seconds to form a uniform mixture;
[0049] S3: Molding: The mixture is molded by a hydraulic molding machine with a pressure of 25MPa to 30MPa and a pressing time of 8 seconds. The density of the brick after molding is 2.45g / cm 3 ~2.60g / cm 3 ;
[0050] S4: Curing: The formed pavement bricks are subjected to moist curing in an environment of 5℃~15℃, with the humidity maintained at 80%~90%. The curing time is 7 to 14 days;
[0051] S5: Performance test. After the curing period, the samples are subjected to compression test according to standard size. During the test, a compression testing machine is used to load the samples until they break. The qualified standard is that the compressive strength of the brick body should be ≥60MPa. The brick body is subjected to 50 freeze-thaw cycles in the freezing and heating cycle process. The freezing process is -18℃ and the melting process is +5℃. The cycle time is 1 hour freezing and 2 hours heating. The quality, compressive strength and appearance of the brick body are measured after each cycle. During the actual implementation process, the expansive agent reacts with the water in the cement to generate expansive hydration products, such as aluminum hydroxide. These expansive products expand during the cement hydration process, filling the tiny pores in the cement matrix and reducing the expansion of cracks generated during the freeze-thaw process. This expansive reaction not only enhances the density of the brick, but also effectively improves the frost resistance of the brick, especially its stability in low temperature and high humidity environments. In addition, nano-silica reacts with calcium hydroxide in cement to generate hydrated calcium silicate gel. These gels form a dense network structure in the cement matrix, filling the micropores and significantly improving the density and impermeability of the brick. The extremely small particles of nano-silica can enhance the microstructure of the cement matrix, making the brick more durable in freeze-thaw cycles. The polymer emulsion forms a strong three-dimensional molecular network structure through cross-linking reaction with cement hydration products. This structure increases the toughness of the brick, significantly improves the crack resistance and ductility of the brick, and reduces microcracks during freeze-thaw. The expansion enhances the impact resistance of the brick body. At the same time, the mineral admixture reacts with calcium ions during the cement hydration process to generate hydration products. This reaction not only improves the structural stability of the brick body, but also reduces the thermal expansion coefficient by reducing the heat release of cement, further reduces the volume change caused by temperature difference changes, and reduces the risk of damage caused by freeze-thaw cycles. The high-pressure molding and low-temperature curing steps of the entire process ensure the high density and uniformity of the brick body, so that the brick body can maintain excellent performance in freeze-thaw cycles and long-term use, avoiding cracks and material aging. Finally, the brick body undergoes a series of performance tests, such as compressive strength, freeze-thaw cycles, water absorption rate and penetration depth tests, etc., to ensure its long-term stability in high-cold, high-humidity and high-traffic frequency environments, meeting the requirements of high-performance pavement materials. Through the synergistic effect and process control between these multiple raw materials, the pavement bricks of the present invention have significant anti-freeze, anti-seepage, anti-cracking and wear-resistant properties in extreme environments, and have good application prospects.
[0052] Optionally, the expansive agent reacts with the moisture in the cement matrix to generate expansive hydration products, and the expansive hydration products fill the tiny pores in the cement matrix. In actual implementation, in the production process of super-strong frost-resistant and anti-permeability artificial pavement bricks, the use of expansive agents plays a very important role. The role of the expansive agent is mainly to chemically react with the moisture in the cement matrix to generate expansive hydration products. These expansive hydration products can effectively fill the tiny pores in the cement matrix, thereby improving the structural density of the cement matrix. Specifically, when the expansive agent reacts with the moisture in the cement matrix, it usually generates expansive hydration products such as hydrated calcium aluminate and calcium aluminate. These products fill and seal the microscopic pores of the cement matrix through expansion, filling The filled pores significantly reduce the micro-cracks in the cement matrix, thereby improving the density and permeability of the cement matrix, which not only enhances the freeze-thaw resistance of the brick body, but also significantly improves its permeability, making the brick body less likely to crack or seep water when encountering severe cold or rainy environments. In addition, the addition of the expansion agent can also reduce the capillary porosity in the cement matrix, thereby reducing the water penetration path, further improving the durability and stability of the pavement bricks. The cement matrix after the expansion agent reaction has stronger frost resistance, because water is not easy to enter the tiny pores, avoiding the destructive effect of water freezing and swelling at low temperatures.
[0053] Optionally, the nano-silica reacts with calcium hydroxide in cement to form calcium silicate hydrate, forming a dense gel network within the cement matrix. In actual implementation, the particle size of nano-silica is typically between 15 and 30 nanometers. This characteristic gives it a large specific surface area and allows it to react with calcium hydroxide (Ca(OH)2) in cement to form calcium silicate hydrate (CSH) gel. Since nano-silica has a very small particle size (15-30 nm), it can penetrate deep into the microstructure of the cement matrix, effectively react with calcium hydroxide, and promote the formation of calcium silicate hydrate in the cement matrix. The formed CSH gel has high cohesion and strong structural stability. Due to the high surface area of nano-silica, it can fill the tiny pores in the cement matrix, further improving the density of the cement matrix.
[0054] Optionally, the polymer emulsion forms a strong molecular network structure by undergoing a cross-linking reaction with cement hydration products. In actual implementation, the polymer molecules in the polymer emulsion have multiple active functional groups and can undergo a cross-linking reaction with cement hydration products (such as hydrated calcium silicate, calcium hydroxide, etc.). This cross-linking reaction causes the polymer molecules to form a three-dimensional molecular network structure in the cement matrix, similar to a "molecular skeleton". This network structure has very good mechanical properties and chemical stability, and can significantly enhance the compressive strength, tensile strength and freeze-thaw resistance of the cement matrix. Through the cross-linking reaction with the cement hydration products, the polymer emulsion can effectively fill the microscopic pores in the cement matrix, further improving its density and water resistance, which makes the overall structure of the cement matrix stronger, reduces the chance of water entering the tiny pores, and thus improves the anti-permeability of the brick body. In addition, the addition of the polymer emulsion also helps to improve the flexibility and crack resistance of the cement matrix. The traditional cement matrix is relatively brittle and easily cracks under the action of external forces. The formation of the polymer molecular network gives the structure of the cement matrix a certain toughness, which can disperse the externally applied stress and reduce the occurrence of cracks. This feature is especially important for freeze-thaw resistance, because the expansion and melting process during the freezing process will produce repeated stress on the cement matrix, and the network structure of the polymer emulsion can effectively reduce the damage to the brick body caused by the freeze-thaw cycle.
[0055] Optionally, the mineral admixture is fly ash or slag, which is mixed with the Ca in cement. 2+ The reaction generates hydration products and reduces the thermal expansion coefficient of the brick by reducing the heat release of cement. In the actual implementation process, the hydration reaction and its effects: fly ash or slag as mineral admixtures can participate in the reaction during the cement hydration process to generate secondary hydration products, which react with the Ca in the cement. 2+ After the ion reaction, the SiO2, Al2O3 and other components released from fly ash or slag will react with Ca 2+ React to form substances such as calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH). These hydration products will enhance the density of the cement matrix and reduce voids, thereby improving the strength and anti-permeability of the brick body;
[0056] Reducing heat release and lowering the thermal expansion coefficient: Mineral admixtures have a significant effect on the heat release of cement. The addition of fly ash and slag usually reduces the hydration reaction heat of cement and reduces the heat generated by the cement matrix during the hardening process. This effect is especially important in large-scale production processes, because excessive heat release may cause temperature stress in the cement matrix, which in turn causes cracks and uneven shrinkage. By reducing heat release, mineral admixtures effectively reduce the internal temperature gradient of the brick body and reduce the stress caused by temperature changes, thereby improving the durability of the brick body.
[0057] Optionally, the mass ratio of the cement to the mineral admixture is:
[0058] The cement: mineral admixture ratio is 1:0.2 to 1:0.5, with the optimal mass ratio being 1:0.3. In actual implementation, 0.3 parts of mineral admixture are added to every 1 part of cement. At this ratio, the combination of cement and mineral admixture can achieve the best performance balance.
[0059] Optionally, after the mixture is formed under high pressure, the flexural strength is ≥7 MPa, and the compressive strength loss of the brick body after 50 freeze-thaw cycles does not exceed 15%. In actual implementation, according to process requirements, the compressive strength loss of the brick body after 50 freeze-thaw cycles should not exceed 15%. This requirement ensures that the brick body will not experience severe strength degradation during the freeze-thaw process. Specifically:
[0060] Freeze-thaw cycle process: In the freeze-thaw cycle, the brick will go through two stages: freezing (-18℃) and melting (+5℃). In each cycle, the brick will be frozen for 1 hour, then heated to +5℃ and maintained for 2 hours. This process is repeated for a total of 50 times;
[0061] Maintenance of compressive strength: After the freeze-thaw cycle, the loss of compressive strength of the brick should be controlled within 15%, that is, the compressive strength of the brick should be maintained at more than 85% of the original strength, which means that the brick has strong resistance to freeze-thaw and is not prone to structural damage due to temperature changes.
[0062] Optionally, the brick has a water absorption rate of ≤3% within 24 hours and a penetration depth of no more than 5 mm. In actual implementation, ensuring that the brick has a water absorption rate of ≤3% within 24 hours and a penetration depth of no more than 5 mm can effectively improve the brick's anti-penetration properties. This improved performance not only enhances the brick's stability in wet or humid environments, but also reduces freeze-thaw damage caused by water intrusion, extending the brick's service life. Furthermore, the low water absorption rate and shallow penetration depth also ensure physical and chemical stability in changing environmental conditions and long-term use.
[0063] The above shows and describes the basic principles, main features and advantages of the present invention, and the standard parts used in the present invention can be purchased from the market, and special-shaped parts can be customized according to the description in the specification and the drawings. The specific connection methods of each part adopt conventional means such as mature bolts, rivets, welding, etc. in the existing technology. The machinery, parts and equipment all adopt conventional models in the existing technology, and the circuit connection adopts the conventional connection method in the existing technology, which will not be described in detail here.
[0064] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's description and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A production process for super-strong frost-resistant and anti-seepage artificial paving bricks, characterized by: The following steps are involved: S1: Raw material preparation: Select the following raw materials and mix them according to mass percentage: Cement: 25% to 35%, using P.O42.5 ordinary Portland cement; Mineral admixture: 15% to 25%, either fly ash or slag; High-strength aggregate: 30% to 45%, a mixture of quartz sand with a particle size of 1 to 3 mm and basalt crushed stone with a particle size of 5 to 10 mm; Expansion agent: 2% to 4%, either bauxite or calcium bauxite; Nano-silicon dioxide: 0.5% to 2%, with an average particle size of 15 to 30 nm; Polymer emulsion: 1% to 3%, which is an acrylic polymer emulsion with a solid content of 45% to 50%; Water: 12% to 16%; S2: Mixing and stirring: pre-mix all the above raw materials according to the mass ratio, dry mix time is 90 seconds, stir in a forced concrete mixer to ensure uniform distribution of the ingredients, then add water and polymer emulsion, wet mix time is 120 seconds to form a uniform mixture; S3: Molding: The mixture is molded by a hydraulic molding machine with a pressure of 25MPa to 30MPa and a pressing time of 8 seconds. The density of the brick after molding is 2.45g / cm 3 ~2.60g / cm 3 ; S4: Curing: The formed pavement bricks are subjected to moist curing in an environment of 5℃~15℃, with the humidity maintained at 80%~90%. The curing time is 7 to 14 days; S5: Performance test. After the curing period, the samples are subjected to compression test according to standard size. During the test, a compression testing machine is used to load the samples until they break. The qualified standard is that the compressive strength of the brick body should be ≥60MPa. The brick body is subjected to 50 freeze-thaw cycles in the freezing and heating cycle process. The freezing process is -18℃ and the melting process is +5℃. The cycle time is 1 hour freezing and 2 hours heating. The quality, compressive strength and appearance of the brick body are measured after each cycle.
2. The production process of a super-strong frost-resistant and anti-permeability artificial paving brick according to claim 1, characterized in that: The expansive agent reacts with water in the cement matrix to generate expansive hydration products, which fill the tiny pores in the cement matrix.
3. The production process of super frost-resistant and anti-permeability artificial paving bricks according to claim 1, characterized in that: The nano-silicon dioxide reacts with calcium hydroxide in cement to generate calcium silicate hydrate, forming a dense gel network in the cement matrix.
4. The production process of super frost-resistant and anti-permeability artificial paving bricks according to claim 1, characterized in that: The polymer emulsion forms a strong molecular network structure by undergoing a cross-linking reaction with cement hydration products.
5. The production process of super frost-resistant and anti-permeability artificial paving bricks according to claim 1, characterized in that: The mineral admixture is either fly ash or slag, which is mixed with the Ca in cement. 2 +The reaction generates hydration products and reduces the thermal expansion coefficient of the brick by reducing the heat release of cement.
6. The production process of super frost-resistant and anti-permeability artificial paving bricks according to claim 1, characterized in that: The mass ratio of the cement to the mineral admixture is: The cement: mineral admixture ratio is 1:0.2 to 1:0.5, and the optimal mass ratio is 1:0.
3.
7. The production process of super frost-resistant and anti-permeability artificial paving bricks according to claim 1, characterized in that: After the mixture is formed under high pressure, the bending strength is ≥7MPa, and the compressive strength loss of the brick body does not exceed 15% after 50 freeze-thaw cycles.
8. The process for producing super-strong frost-resistant and anti-permeability artificial pavement bricks according to claim 1, characterized in that: The water absorption rate of the brick body within 24 hours is ≤3%, and the penetration depth does not exceed 5mm.
Citation Information
Cited By
High-performance concrete pavement brick and preparation method thereof
CN120829284A
High performance concrete pavement tile and method of making same
CN120829284B